NEW TECHNOLOGIES AND GENRE VARIATION. PRINTED AND ELECTRONIC DOCUMENTS IN TERTIARY EDUCATION ESP’ COURSES - Fernandez Toledo, Piedad (International Journal of English Studies, 2002)
New technologies are as present nowadays in university as they are in society in general, influencing all aspects OS the teaching-learning dynamics. Within this electronic environment new genre types have arisen which should be as familiar to students as computers themselves. In this chapter the impact of technologies on genre variation is discussed, especially in relation to aulthentic malerial as teaching support. This influence is shown in a specific ESP area, that OS English For Library and lnformation Science (LIS), examining the possibilities, based on the relationship between older and newer genres, that are brought into the classroom. An example of changes brought about by Information Technologies on a classroom project is given: this now involves using web sites as a resource for the construction of leaflets. Following this, some advantages derived from its implementation during two academic years are discussed. The conclusions point to the benefit that new genre exploration in the ESP classroom offers for the building of academic literacy at tertiary level.